Your Job in Germany - Capra, Frank (United States, 1945)
“Your Job in Germany” is a short film made for the United States War Department in 1945. It was intended to be shown to U.S. soldiers about to occupy Germany. The film urged against fraternization with the German people, who are portrayed as thoroughly untrustworthy. It reminds its viewers of Germany's history of aggression, under "Führer Number 1" Otto von Bismarck, "Führer Number 2" Kaiser Wilhelm II and "Führer Number 3" Adolf Hitler. It argues that German youth were especially dangerous because they had spent their entire lives under the Nazi regime.